Three new Early Middle Eocene Bats (Mammalia: Chiroptera) from Elderberry Canyon, Nevada, USA - Czaplewski, Nicholas J.; Morgan, Gary S.; Emry, Robert J. 1940-; Gignac, Paul M.; O'Brien, Haley D. (Smithsonian Scholarly Press, 2022)
Volactrix simmonsae gen. et sp. nov. -- Palaeochiropteryx sambuceus sp. nov. -- Sonor handae gen et sp. nov.
Includes bibliographical references
Keywords: Säugetiere; Flattertiere; Elderberry Cañyon; Bats, Fossil / Nevada / Elderberry Canyon; Paleontology / Nevada / Elderberry Canyon / Eocene